Profit planning decisions with the break-even system - Tucker, Spencer A. (England : Gower publishing company limited, 1981)
The book gives simple tools for obtaining a picture of the profit structure so that the best possible decisions can be made on current questions involving: pricing, product mix selection, territorial profitability, expansions, justifications of expenditures, and decisions involving make or buy, return on capital employed, sales compensation, etc.
Includes bibliographical references and index.
hza 01/08/2018
Loans
Keywords: Profit-accounting.; Break-even analysis